Implementasi Penghapusan Piutang PBB-P2 Yang Sudah Kadaluarsa Di Kota Bukittinggi - Anggraweni, Mutia; Ariany, Ria; Ameliza, Kiki (CV. ITTC INDONESIA, 2021)
The movement of the realization of the reduction in uncollectible accounts in Bukittinggi did not change significantly, because the execution only started processing in 2020 after BPK finds it. The process of eliminating uncollectible accounts that have expired is where data rearrangement or updating is carried out first, but in fact the Bukittinggi City Government does not do it due to a shortage of human resources. It can indirectly provide a negative picture of the performance of Bukittinggi City Government. This research is a descriptive research with a qualitative approach. The types of data used in this study are primary data and secondary data. The data collection technique used was obtained by field research and library research. Data analysis was carried out by qualitative analysis and using purposive sampling technique in determining the sources. Testing the validity of the data is done by triangulation method. The results showed that the implementation of the policy for the write-off of PBB-P2 receivables that had expired at the Bukittinggi City Finance Agency when viewed from the Eward III theory had not been implemented optimally. In terms of communication, there are still shortcomings and in terms of resources there are deficiencies both in terms of quantity and quality.The focus of attention is the implementation of the Mayor of Bukittinggi Regulation Number 11 of 2014 so that it can be successfully implemented to overcome the problem of expired land and building tax receivables in rural and urban areas.